2023
DOI: 10.3390/app13063959
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Challenges in Design of Connections in Steel-Braced Frame Systems with In-Plane Buckling Braces

Abstract: A new type of connection has been developed for steel-braced frame systems that allows the brace members to undergo compression buckling in the in-plane direction. In addition to the inherent benefits of in-plane buckling (IPB) braces that help in reducing the extent of damage to the non-structural components, the IPB brace system is also considered to be an efficient way of retrofitting existing seismically deficient structures. The use of the compact and thicker gusset plate prevents the distortion of the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…One type of building that has not received much attention in this area is braced steel buildings, which are most commonly used lateral force resisting system and are particularly vulnerable to low-cycle fatigue induced by seismic damage [9][10][11]. Therefore, the objective of this study is to investigate how earthquake duration affects the seismic performance of steel braced frames, with a particular focus on the effects of low-cycle fatigue behaviour of the open section braced members.…”
Section: Long Duration Earthquakesmentioning
confidence: 99%
“…One type of building that has not received much attention in this area is braced steel buildings, which are most commonly used lateral force resisting system and are particularly vulnerable to low-cycle fatigue induced by seismic damage [9][10][11]. Therefore, the objective of this study is to investigate how earthquake duration affects the seismic performance of steel braced frames, with a particular focus on the effects of low-cycle fatigue behaviour of the open section braced members.…”
Section: Long Duration Earthquakesmentioning
confidence: 99%
“…Previous seismic events have revealed that brace frame systems are vulnerable to premature collapse. Several undesirable failure modes, including the fracture of the interface weld of the gusset plate, tearing of the gusset plate, buckling of the gusset plate, net section failure of the brace cross-section, and premature failure of the brace section, have been observed [16]. Based on the data gathered from both real seismic events and experimental assessments [17][18][19][20], it has been determined that there are three specific locations within the braced frame that are susceptible to damage [19].…”
Section: Introductionmentioning
confidence: 99%